Pharmacist-led intervention reduced drug-related problems in the management of type 2 diabetes mellitus patients - Wahyudi Wahyudi; Azizah Nasution; Dharma Lindarto; Khairunnisa Khairunnisa (Pharmacia)
This pre- and post-quasi-experimental study was undertaken to analyze the impact of pharmacist-led intervention (PI) on the reduction of DRPs in the management of type 2 diabetes mellitus outpatients (n = 106) for six months admitted to Prof. Dr. Chairuddin P. Lubis Hospital, Medan, Indonesia. The required data of patients in the control group (CG) and PI groups were extracted from medical records. DRPs were analyzed by applying PCNE version 9.1. The significance of PI on DRPs was analyzed using a paired t-test. The mean age of the patients was 58.61 ± 8.89 (years). Most (54.72%) of them were female. The total incidences of DRPs in CG and PI groups were 263 and 205, respectively, (p = 0.001). The relative risk of PI on DRPs was 0.93 and the absolute risk reduction was 6.6%. This study indicated that PI through patient counseling reduced the incidence of DRPs in the management of T2DM outpatients.